Kerkordelike toleransie en die reg van usansie - Wyk, Barry J. van (HTS teologiese studies, 2020)
A tolerant treatment of church order and the law of usance: This article discusses the recent decline of church polity in the Netherdutch Reformed Church which is obvious in different areas of the Church with special reference to the liturgy practised in sermons of some congregations. This decline is also observed in other churches in South Africa and abroad. The article is a reaction to the reason for this situation and indicates that it should not be found in a collegialistic concept of church, but rather due to congregationalism or independentism in modern form. The article’s viewpoint is that the above-mentioned church polity decline is a result of the fact that church order is not valued as an order with a Scriptural and therefore an ecclesiological basis.